A Government-Binding Analysis of VP Sentential Complements in Egyptian Arabic - Talaat, Hala M. (Linguistica Atlantica, 1987)
This paper examines VP sentential complements in Egyptian Arabic- within a Government and Binding framework. Various types of finite and non-finite sentential complements are identified according to the distribution of the complementizer ?inn ’that’ and the elements that fill the complement subject position. It is proposed that Case and Binding parameters are set differently in Egyptian Arabic than in English. In Egyptian Arabic, certain subject NPs are potentially Case-marked by two categories. In these instances the lexical Case-marker prevails, thereby establishing the governing category for the NP, and determining the NP’s range of interpretation by the Binding principles.